Explicitation strategy in the translation of ‘Rihlah Ibn Battutah’ into English - Yaakob, Nor Azuwan; Syed Abdullah, Syed Nurulakla; Abd Kadir, Kasyfullah; Boudville, Audrey Geraldine; Mohd Yasin, Badrul Hisyam (Human Resource Management Academic Research Society, 2020)
In translation, the utterances delivered in the form of implicit meaning in Arabic are not necessarily retained in the same form in English which results in a reversal, with the form of implicit meaning being translated into explicit meaning. This study aims to identify the forms of implicit meaning in the book entitled Rihlah Ibn Battutah, explore the influence of culture on this translation, and analyse the strategies used by the translator to deal with the difficulties of translating implicit meaning. The qualitative methodology was adopted using the case study and textual analysis methods based on the approach proposed by Klaudy and Karoly (2005), and Pym (2004). Data analysis was carried out using the ATLAS.ti software. The results show that explicitation in translation is not only driven by cultural factors in general, but is also significantly influenced by other factors that include religion, Arabic Rhetorical Sciences (Bal?ghah), lexicogrammatical and pragmatic dimensions, communicative preferences, and language politeness. It is hopeful that this study will spark interest in the study on the explicitation strategy in the field of translation.